Application of the Greedy Algorithm for Graph Coloring of the Grobogan Regency Map: Application of the Greedy Algorithm for Graph Coloring of the Grobogan Regency Map - Ade Ima Afifa Himayati; Muhammad Adib Jauhari Dwi Putra; Erik Maurten Firdaus; Muhammad Faudzi Bahari (Eigen Mathematics Journal, 2022)
The district map in Grobogan Regency can be optimized using the Greedy algorithm. The point on the graph represents the district and the line represents two areas that are directly adjacent. Greedy Algorithm is one of the algorithms developed to solve the problem of graph coloring to be able to produce minimal colors that are used without having the same color in areas that are directly adjacent. Greedy’s algorithm uses a set of color candidates and solutions in its solution. Staining is done at the point with the greatest degree followed by an examination of the appropriateness of the color with the principle that no neighboring points have the same color. The resulting color is included in the solution set. The process is continued until all the dots have been colored. Regional coloring in Grobogan district produces four colors with a greedy algorithm as the minimum color solution obtained